The empathic civilization the race to global consciousness in a world in crisis - Rifkin, Jeremy (J.P. Tarcher/Penguin, 2009)
Bestselling social critic Jeremy Rifkin shows that the disconnection between our vision for the world and our ability to realize that vision lies in the current state of human consciousness.